(untitled) (National Administration Journal, 2017)
This research analyzes the individual determinants of the decision to participate in the stock market in eight European countries - France, Germany, Italy, the Netherlands, Poland, Spain, Sweden and the United Kingdom, on a sample of 6,036 individuals, aged between 18-65 years. The data used in the empirical analysis comes from the study “The EU Market for Consumer Long Term Retail Saving Vehicles. Comparative Analysis of Products, Market Structure, Costs, Distribution Systems and Consumer Saving Patterns”, carried out by the European Commission in 2007. The main focus of this paper consists of analyzing the potential gender gap in stock market participation while it includes socioeconomic variables that have already been studied in the prior financial literature focused on other countries, as well as behavioral determinants that have not been analyzed in depth so far. The results highlight that stock market participation in the countries above mentioned. Issues positively related to this research involves: peoples age, being male, having university studies, income, influence of financial advice and willingness to risk; and a negatively related issue is seeking of financial advice and general trust. Besides, it is important the existence of institutional country factors that influence the investors’ attitudes toward stockholding.